THE INFLUENCE OF TRANSLATION STUDIES ON MODERN PHILOLOGICAL RESEARCH - Turg`unboyeva Hilola No`mon qizi Superviser: Kenjayeva Muxlisa Baxodirovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Translation studies has significantly influenced modern philological research, reshaping how scholars approach language, literature, and culture. This article explores the interdisciplinary impact of translation studies, focusing on its contributions to textual interpretation, linguistic analysis, and cultural understanding. By emphasizing the subjectivity of translation and the role of translators as co-creators, translation studies challenges traditional notions of textual authenticity and meaning. Concepts like equivalence, untranslatability, and cultural translation have advanced philological methodologies, particularly in analyzing multilingual and postcolonial texts. Key words: translation studies,linguistic analysis,textual interpretation, cultural understanding .